First, get your quadratic equation to the form
color(blue)(x^2 + b/ax = -c/a)x2+bax=−ca
To do that, add 55 to both sides of the equation
x^2 + 2x - color(red)(cancel(color(black)(5))) + color(red)(cancel(color(black)(5))) = 5
x^2 + 2x = 5
Next, divide the coefficient of the x-term by 2, square the result. then add it to both sides of the equation.
2/2 = 1, then 1^2 = 1
This will get you
x^2 + 2x + 1 = 5 + 1
Notice that you can rewrite the left side of the equation as the square of a binomial
x^2 + 2x + 1 = x^2 + 2 * (1) * x + 1^2 = (x+1)^2
You will now have
(x + 1)^2 = 6
Take the square root of both sides
sqrt((x+1)^2) = sqrt(6)
x + 1 = +- sqrt(6) => x_(1,2) = -1 +- sqrt(6) = {(x_1 = color(green)(-1 - sqrt(6))), (x_2 = color(green)(-1 + sqrt(6))) :}